Efficiency enhancement study on addition of 1-hexyl-3-methylimidazolium iodide ionic liquid to the poly(methyl methacrylate-co-methacrylic acid) electrolyte system as applied in dye-sensitized solar cells - Sundararajan, V.; Farhana, N.K.; Ng, H.M.; Ramesh, Subramaniam; Ramesh, Kasi (Elsevier, 2019)
The replacement of liquid electrolytes with gel polymer substituents in dye-sensitized solar cells (DSSCs) has become an accepted strategy not only to overcome problems encountered previously but also to increase the shelf life and photovoltaic performance of DSSCs. In that perspective, a gel polymer electrolyte system based on poly(methyl methacrylate-co-methacrylic acid), P(MMA-co-MAA), was prepared with iodine/iodide redox mediator from a sodium salt and the commercially available ionic liquid 1-hexyl-3-methylimidazolium iodide (HMIm + I − ) and was studied for its ionic conductivity and energy conversion efficiencies along with structural investigation of the complex by Fourier transform infrared spectroscopy and X-ray diffraction. The highest conductivity achieved was 2.33 mS cm −1 at room temperature for the gel polymer electrolyte with 20 wt% HMIm + I − . With a generic DSSC arrangement of TiO 2 sensitized with N719 dye photoanode/electrolyte/Pt-containing counter electrode, the copolymer-based conducting electrolyte displayed power conversion efficiency of 5.30% under illumination of 100 mW cm −2 . © 2019 Elsevier Ltd